Semejanza interpretativa en «Elegía escrita sobre el cementerio de una aldea» (1822), de Manuel Norberto Pérez de Camino. Interpretive resemblance in «Elegía escrita sobre el cementerio de una aldea» (1822), by Manuel Norberto Pérez de Camino - Rosalía Villa Jiménez (Hermeneus, 2024)
According to Relevance Theory (Sperber and Wilson, 1986) applied to translation ( Gutt, 1989, 2014), the role of the translator is to encourage the target audience to grasp the intended information, following the communicative and cognitive principles of relevance. The target text must be ostensive and highly relevant, so that the effort to process the information given may be rewarded with a significant number of positive cognitive effects. Gutt suggests the indirect translational mode, which enables the translator to achieve an incomplete interpretive resemblance with regards to the source text.